An Integrated Neuronal Model of Claustral Function in Timing the Synchrony Between Cortical Areas - Vidyasagar, Trichur R.; Levichkina, Ekaterina (Frontiers in Neural Circuits, 2019)
It has been suggested that the function of the claustrum may be to orchestrate and integrate the activity of the different cortical areas that are involved in a particular function by boosting the synchronised oscillations that occur between these areas. We propose here a model of how this may be done, thanks to the unique synaptic morphology of the claustrum and its excitatory and inhibitory connections with most cortical areas. Using serial visual search as an example, we describe how the functional anatomy of the claustral connections can potentially execute the sequential activation of the representations of objects that are being processed serially. We also propose that cross-frequency coupling between low frequency signals from claustrum and higher frequency oscillations in the cortical areas will be an efficient means of claustrum modulating neural activity across multiple brain regions in synchrony. This model is applicable to the wide range of functions one performs, from simple object recognition to reading and writing, listening to or performing music, etc.